AKUNTANSI MUDHARABAH: PERSPEKTIF SYARIAH DAN IMPLEMENTASINYA DALAM LAPORAN KEUANGAN BANK SYARIAH - Maulena Maulena; Mona Fitri; Naila Afifah Sharfina; Yusri Hazmi; Mariana Mariana (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the implementation of mudharabah accounting in Islamic banks based on sharia principles, the Sharia Financial Accounting Standards (SAK Syariah), and the characteristics of mudharabah financing. The main focus of the study is to understand how profit and loss sharing is conducted fairly between shahibul maal and mudharib, as well as the role of agency theory and trust theory in enhancing transparency and reducing moral hazard risks in Islamic bank financial statements. The research method used is a literature review, analyzing various sources related to mudharabah accounting and the implementation of SAK Syariah, such as books, scientific journals, and research reports. The analysis process is descriptive, synthesizing the key findings from the selected literature based on relevance and authority. The study results indicate that the implementation of mudharabah accounting must ensure that sharia principles are maintained, while emphasizing transparency and accountability in financial reporting. Additionally, the role of supervision and trust between shahibul maal and mudharib is crucial in maintaining an efficient and fair relationship. This research also evaluates how mudharabah accounting contributes to the sustainability of the Islamic banking industry and provides recommendations for improving financial reporting and strengthening trust in the sharia investment system.